Das Mindestlohngesetz: Hoffnungen und Befürchtungen - Joachim Möller; Karl Brenke; Gert G. Wagner; Thorsten Schulten; Gustav Horn; Hagen Lesch; Alexander Mayer; Lisa Schmid; Patrick Arni; Werner Eichhorst; Alexander Spermann; Klaus F. Zimmermann (Wirtschaftsdienst, 2014)
Der Bundestag wird das Mindestlohngesetz voraussichtlich Anfang Juli 2014 verabschieden. Ab Januar 2015 soll eine Lohnuntergrenze von 8,50 Euro pro Stunde eingeführt werden und mit wenigen Ausnahmen fl ächendeckend gelten. Diskutiert wird, welche Folgen der Mindestlohn auf die Beschäftigung und die Lohnentwicklung haben wird. Der Anpassungsdruck in Ostdeutschland wird durch das niedrigere Lohnniveau viel höher ausfallen, so dass eine regionale Staffelung geboten sein kann. Europäische Nachbarländer haben zudem gute Erfahrungen mit niedrigeren Jugendmindestlöhnen gemacht, damit die Ausbildungsneigung nicht abnimmt. Die Evaluation des Gesetzes ist erst für 2020 vorgesehen, während damit nach Auffassung der Autoren besser gleich begonnen werden sollte. – – The German government plans to introduce a minimum wage from 2015. This must be understood as a response to the decline in collective bargaining coverage and the marked increase in employment in the low-wage sector. The authors discuss how many workers are affected by this new regulation and whether the minimum wage is too high in relation to the average wage of workers (Kaitz index). They assume that the introduction of a minimum wage in Germany can have a number of effects. It is not possible to forecast all the reactions and behaviour of market participants to handle higher wages and goods prices. Some authors warn that these measures are significant labour market interventions that could have adverse employment effects. They recommend allowing more exemptions from the minimum wage law than intended by the government, especially for young employees and student apprentices. Other authors hope that minimum wages would help to strengthen collective bargaining and stabilise wages. Some authors emphasise that there should be a careful evaluation of the economic effects by scientists.
Keywords: J21; J31; J38; 330